Interpretation of genre and subject scope and poetics of Jadid literature (Journal of Science-Innovative Research in Uzbekistan, 2024)
One of the most important events in the cultural and spiritual life of Turkestan modernism is the appearance of the new literature of Turkestan. As we know, a new generation has entered the field of our literature since the 1990s. This period is characterized by a number of talents such as Hamza Hakimzada Niyazi, Mirmuhsin, Avloni, Behbudi. This generation gave up the old way of thinking and gave up completely new ideas and views about social life and the role of art in society.